ANALISIS PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN MAHASISWA PENGGUNA GORIDE GOJEK DI KABUPATEN DELI SERDANG - Armando, Rocky; Hendra, Hendra; Matondang, Vinsensius (Universitas Of Surakarta, 2020)
The development of business in the online transportation sector is in great demand by the public. In this case, the researcher conducted research on one of the online transportation companies, namely Gojek. This research aims to determine and analyze the effect of price and service quality on student satisfaction of Gojek goride users in Deli Serdang Regency. The type of research used is quantitative research. The sampling technique used is nonprobability sampling technique with accidental sampling approach. Data were collected using a questionnaire / questionnaire with a sample of 100 respondents. This study uses multiple linear regression analysis methods, and hypothesis testing is carried out using the T test and F test. The results of the study using the T test show that price (X1) has a positive effect on student satisfaction (Y), while the quality of service (X2) has a positive and significant effect on student satisfaction (Y). This shows that the service quality variable (X2) has a dominant influence in influencing student satisfaction (Y). While the F test price (X1) and service quality (X2) simultaneously affect student satisfaction by comparing. And this can also be seen from the value of the Adjusted R Square, which is 0.665.